Digital Finance Adoption, Emerging Trends, and Customer Satisfaction: A Bibliometric Analysis - Shakya , Rosma; Karki , Dipendra (Journal of Innovation in Academia, 2025)
The rapid advancement of digital finance has transformed global financial systems, making understanding research trends and customer satisfaction crucial. This study employs bibliometric analysis using Dimensions data to examine research trends, collaboration patterns, and thematic focuses in digital finance adoption. The analysis reveals a steady growth in publications on trust, security, convenience, and service quality. Top journals like the International Journal of Information Management are highly referenced, demonstrating academic interest in user-centric digital finance research. Co-authorship analysis shows remarkable collaboration in this field, with 2.56 authors per document. International collaboration is limited (7.45%), showing a predominance of national or regional studies. This shows cross-border research can improve global knowledge exchange. The study’s findings are significant for researchers, policymakers, and digital service providers seeking customer-centric strategies. Despite geographical differences and minimal interdisciplinary collaboration, future research should address data security, privacy, and evolving regulatory requirements, improve cross-sector relationships, and enhance global collaboration.